Author's Acceptance in Relating Reader’s Response to Digital Novels - Trie Utari Dewi; Ade Hikmat; Prima Gusti Yanti; Sukardi Sukardi (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Technology development in the digital era has transformed the world of literature, particularly for digital novels. The comment sections on digital literature provide a platform for direct interaction between authors and readers, which can influence the author's creative process. Therefore, this research aims to examine the author acceptance in responding to readers' feedback on their digital novels and to explore its impact on the creative process of the works produced. This study employed a descriptive qualitative method with a literary reception approach to understand readers' responses to three digital novels: "BarraKilla" by Nova Adhita, "Paradise Garden" by Khojina, and "Abi Ghea" by Chelsea Karina. Data were collected through documentation techniques and online observations of readers' comments, then it was analyzed using content analysis techniques and was validated through author interviews. The results of this study showed that readers' responses to digital novels are categorized into three aspects: domination, negotiation, and opposition. Dominant reception can support the plot and strengthen the narrative, while negotiation and opposition receptions can be considered in adjusting the story and evaluating it for the author. This study concludes that digital novel authors respond to readers' feedback through domination, negotiation, and opposition, where this interaction influences the story's development and creates a dynamic relationship between the author and the reader.